2020
DOI: 10.1002/adma.201908275
|View full text |Cite
|
Sign up to set email alerts
|

A Chemically Stable Hofmann‐Type Metal−Organic Framework with Sandwich‐Like Binding Sites for Benchmark Acetylene Capture

Abstract: The realization of porous materials for highly selective separation of acetylene (C2H2) from various other gases (e.g., carbon dioxide and ethylene) by adsorption is of prime importance but challenging in the petrochemical industry. Herein, a chemically stable Hofmann‐type metal−organic framework (MOF), Co(pyz)[Ni(CN)4] (termed as ZJU‐74a), that features sandwich‐like binding sites for benchmark C2H2 capture and separation is reported. Gas sorption isotherms reveal that ZJU‐74a exhibits by far the record C2H2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
242
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 265 publications
(265 citation statements)
references
References 59 publications
8
242
0
Order By: Relevance
“…The purification of acetylene (C 2 H 2 ) gas from natural gas such as CO 2 , CH 4 is of great interest due to its industrial utility. With this attention, J. Pei and coworkers reported that Hofmann based metal–organic framework (named as Co(pyz)[Ni(CN) 4 ], pyz = pyrazine; ZJU-74) shows selective separation of acetylene over CO 2 , C 2 H 4 and CH 4 at ambient conditions [200] . Interestingly, the material possesses high C 2 H 2 capturing capacity (49 cm 3 g −1 at 0.01 bar and 296 K) and high selectivity over CO 2 (36.5 cm 3 g −1 at 1 bar, 296 K), which is the highest selectivity so far.…”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
“…The purification of acetylene (C 2 H 2 ) gas from natural gas such as CO 2 , CH 4 is of great interest due to its industrial utility. With this attention, J. Pei and coworkers reported that Hofmann based metal–organic framework (named as Co(pyz)[Ni(CN) 4 ], pyz = pyrazine; ZJU-74) shows selective separation of acetylene over CO 2 , C 2 H 4 and CH 4 at ambient conditions [200] . Interestingly, the material possesses high C 2 H 2 capturing capacity (49 cm 3 g −1 at 0.01 bar and 296 K) and high selectivity over CO 2 (36.5 cm 3 g −1 at 1 bar, 296 K), which is the highest selectivity so far.…”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
“…[1,2] C 2 H 2 is produced primarily from methane( CH 4 )t hermal pyrolysis or hydrocarbon cracking, whichu sually coexists with some carbond ioxide (CO 2 )a nd CH 4 molecules. [3][4][5] This fact makes the separation of C 2 H 2 from C 2 H 2 and CO 2 or C 2 H 2 and CH 4 very importanti nC 2 H 2 industry.C urrent C 2 H 2 separation technology mainly relieso nt raditional refrigerant distillation. But for C 2 H 2 and CO 2 ,d ue to close boilingp oints (C 2 H 2 189.3 K, CO 2 194.7 K), almoste qual size (3.3 3.3 5.7 3 for C 2 H 2 and 3.2 3.3 5.4 3 for CO 2 )a nd identical linear shape, [6,7] the cost and energy consumptionof distillation method are very high.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Cage Bc onsists of twenty TDC and eight SBUs, which forms a M 8 L 12 cuboid polyhedron with the void dimensions of ca. 15.7 12.8 9.2 3 (Figure 2b). Cage Cr esultsf rom the interlinkage between two MBBs and four TDC, which produces an M 8 L 10 subunit with the cavity sizes of ca.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recently developed MOFs offer the potential of use in adsorptive separations of C 2 H 2 /CO 2 mixtures. 40 53 …”
Section: Introductionmentioning
confidence: 99%